Role of Indian Association of Preventive and Social Medicine in Community Based Palliative Care - A Position Statement - Srikanth Srinivasan; Vinayagamoorthy Venugopal; Suguna Elayaperumal; Mahendra Singh; Priya Kataria; Rehana Vanaja Radhakrishnan (Indian Journal of Community Medicine)
Currently, access to palliative care is a challenge for the majority of people with serious health suffering in India. Most of the existing palliative care services are available at tertiary healthcare facilities in urban areas. The National Program of Palliative Care (NPPC) envisages incorporating palliative care in undergraduate medical education to improve the knowledge and skills of primary care physicians to provide quality palliative care in the home setting of patients. Additionally, NPPC also aims to promote community awareness and ownership in palliative care. Community-based palliative care (CBPC) provides holistic support for patients with serious illnesses. This position statement intends to address possible considerations on the role of the Indian Association of Preventive and Social Medicine (IAPSM) on CBPC in the country. A team of members of IAPSM trained in essential palliative care attempted to develop this position statement. The team explored the existing status of palliative care in India and feasible solutions through IAPSM for CBPC by the objectives of NPPC. The team applied and analyzed the WHO framework of public health approach to palliative care – amalgamation in primary health care, integration with specialists for continuum of care, public awareness, training of primary care physicians and community volunteers, and supportive supervision in community initiatives. IAPSM can effectively contribute to CBPC through capacity building of the primary health care team, awareness generation, promoting community ownership, and development of standards of care through community-based research. Implementing the aforementioned recommendations would contribute to achieving the target of Sustainable Development Goal 3.8, which addresses the need for pain relief and palliative care to all needy patients. The IAPSM recognizes palliative care as a vital component of Universal Health Coverage and holds the capacity to bring about substantial changes in the promotion of CBPC in India.